2002
DOI: 10.1098/rsta.2002.1027
|View full text |Cite
|
Sign up to set email alerts
|

The influence of land-use change and landscape dynamics on the climate system: relevance to climate-change policy beyond the radiative effect of greenhouse gases

Abstract: Our paper documents that land-use change impacts regional and global climate through the surface-energy budget, as well as through the carbon cycle. The surface-energy budget effects may be more important than the carbon-cycle effects. However, land-use impacts on climate cannot be adequately quantified with the usual metric of 'global warming potential'. A new metric is needed to quantify the human disturbance of the Earth's surface-energy budget. This 'regional climate change potential' could offer a new met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
395
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 692 publications
(425 citation statements)
references
References 20 publications
(22 reference statements)
7
395
0
6
Order By: Relevance
“…Land use/land cover change mechanisms include both transformation of natural land surfaces to those serving human needs (i.e., direct anthropogenic change; e.g., conversion of tropical forest to agriculture) as well as changes in land cover on longer time scales that are due to biogeophysical feedbacks between atmosphere and land (i.e., indirect change; Cramer et al 2001;Foley et al 2005). Global and regional models have been used extensively to investigate effects of direct and indirect land use/land cover change mechanisms on climate (Copeland et al 1996;Betts 2001;Eastman et al 2001;Pielke et al 2002;Feddema et al 2005). However, all of these studies have focused on land use/land cover related to changes in vegetation types.…”
Section: Introductionmentioning
confidence: 99%
“…Land use/land cover change mechanisms include both transformation of natural land surfaces to those serving human needs (i.e., direct anthropogenic change; e.g., conversion of tropical forest to agriculture) as well as changes in land cover on longer time scales that are due to biogeophysical feedbacks between atmosphere and land (i.e., indirect change; Cramer et al 2001;Foley et al 2005). Global and regional models have been used extensively to investigate effects of direct and indirect land use/land cover change mechanisms on climate (Copeland et al 1996;Betts 2001;Eastman et al 2001;Pielke et al 2002;Feddema et al 2005). However, all of these studies have focused on land use/land cover related to changes in vegetation types.…”
Section: Introductionmentioning
confidence: 99%
“…Land-use changes are currently taking place at an unprecedented scale and contribute significantly to changing the local and regional climates. Previous studies have even shown that changes in surface landuse may have a significantly larger impact on climate than anthropogenic greenhouse gases (Pielke et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…LULC composition and change has already been linked to water quality declines (Foley et al, 2005), climate change at regional and global scales (Bonan, 1997, Lawrence & Chase, 2010Pielke et al, 1999Pielke et al, , 2002Pitman et al, 2011), carbon dioxide emissions (Houghton & Hackler, 2001), habitat loss (Seabloom, Dobson, & Stoms, 2002;Soule, 2001), species extinction (Davies et al, 2006), and declining air quality (Romero, Ihl, Rivera, Zalazar, & Azocar, 1999;Ross et al, 2006 between policy decisions, regulatory actions, and land use (Hostert et al, 2011;Lunetta, Knight, Ediriwickrema, Lyon, & Worthy, 2006). Continuous LULCC monitoring allows researchers to draw connections between land change and variables such as carbon storage, watershed protection, and other ecosystem services -information essential for the management of natural and anthropogenic resources.…”
Section: Resultsmentioning
confidence: 99%